The influence of physical training modalities on basal metabolic rate and leptin on obese adolescent boys - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2018)
The aim of this study was to investigate the effects of physical training modalities on basal metabolic rate, cardiovascular fitness and serum leptin level in obese adolescent boys. Sixteen obese adolescent boys (age: 16.81 +/- 0.91 years) were randomly assigned to either resistance (RTG) (n=8) or endurance (ETG) (n=8) training and followed the respective training programmes for six months (3 days/wk, 60 min/day). Leptin, basal metabolism rate (BMR), and maximum oxygen consumption (VO2max) were evaluated at the beginning and end of the intervention. After the training period, Leptin was decreased and VO2max was increased in both groups (p<0.05), whereas BMR was statistically increased only in ETG (p<0.05). These results indicated that both types of exercises had positive effects on cardiovascular fitness and hormonal control of fat metabolism in obese male adolescents. Resistance exercises should be considered as an alternative or supplementation to endurance exercises in youth obesity management.
Keywords: Resistance Training; Endurance Training; Leptin; Basal Metabolic Rate; Obesity; ADIPONECTIN; INTENSITY; EXERCISE